Comparison of four methods for assessment of severity of hand eczema - Agner, Tove; Jungersted, Jacob Mutanu; Coenraads, Pieter-Jan; Diepgen, Thomas L. (Contact dermatitis, 2013)
Background Several instruments for the assessment of the severity of hand eczema and health-related quality of life (HR-QoL) related to hand eczema have been developed. Objectives The aim of the present study was to evaluate the correlation between frequently used methods. Methods Consecutive patients with current hand eczema from three different centres participated in the study. Severity of hand eczema was assessed with the Hand Eczema Severity Index (HECSI), the Physician Global Assessment (PGA), the Clinical Photo Guide, and the Dermatology Life Quality Index (DLQI). Results One hundred and nineteen patients with hand eczema were included in the study. All six pairwise correlation coefficients between the tested methods were highly statistically significant. Correlation was highest between the HECSI and the PGA (r = 0.82), and weakest, although still statistically significant, between the DLQI and the other three severity scores (r between 0.30 and 0.45). Age and frequency of eruptions did not influence the correlations. With respect to sex, there was a tendency for correlation between methods to be higher for men than for women. Conclusion We found an overall positive correlation between the four severity assessments applied. As the weakest correlation was found between the DLQI and the other methods, it is suggested that measurement of HR-QoL should be included for assessment of the severity and consequences of hand eczema, but the finding also indicates that a disease-specific tool for evaluation of HR-QoL in hand eczema patients is needed.